Sequential versus simultaneous market: The relevant antitrust market for salmon - Niels Haldrup; Peter Møllgaard; Claus Kastberg Nielsen (Copenhagen Business School (CBS), Department of Economics, 2005)
Delineation of the relevant market forms a pivotal part of most antitrust cases. The standard approach is sequential. First the product market is delineated, then the geographical market is defined. Demand and supply substitution in both the product dimension and the geographical dimension will normally be stronger than substitution in either dimension. By ignoring this one might decide first to define products narrowly and then to define the geographical extent narrowly ignoring the possibility of a diagonal substitution. These reflections are important in the empirical delineation of product and geographical markets. Using a unique data set for prices of Norwegian and Scottish salmon, we propose a methodology for simultaneous market delineation and we demonstrate that compared to a sequential approach conclusions will be reversed.
hdl:10398/7633
Keywords: C30; K21; L41; Q22; 330; Relevant market; econometric delineation; salmon